2022
DOI: 10.1038/s41598-022-21076-9
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal challenges of tropical bats in temperate zones

Abstract: To examine the challenges faced by free-ranging Rousettus aegyptiacus living at the northern edge of their distribution, we performed a retrospective analysis of 2196 clinical cases reported by a bat rescue NGO over a period of 36 months, from throughout Israel. All cases of injured bats were evaluated and categorized according to date, place, sex, age, and etiology of the morbidity. The data analysis revealed an increase in all types of morbidity during the wintertime, with more than two-fold the number of ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…The number contrasts with findings in northern Germany, relatively closer to our study area, where bats caught outside the shelter during their activity period showed higher coronavirus prevalence [ 25 ]. The low prevalence in the colony studied here might be due to unfavorable physiological and behavioral conditions during bats' hibernation period, including a drop in bat's heart rate from 200 to 300 beats per minute to as low as 10 beats per minute and suspension of breathing for several minutes at a time, which might affect viral replication and reduce bats overall mobility and interactions, thereby decreasing the probability of virus transmission [ 27 ]. Contrary to our results, Subudhi et al (2017) found coronavirus persistence for up to 4 months in North American little brown bats during hibernation in laboratory settings [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The number contrasts with findings in northern Germany, relatively closer to our study area, where bats caught outside the shelter during their activity period showed higher coronavirus prevalence [ 25 ]. The low prevalence in the colony studied here might be due to unfavorable physiological and behavioral conditions during bats' hibernation period, including a drop in bat's heart rate from 200 to 300 beats per minute to as low as 10 beats per minute and suspension of breathing for several minutes at a time, which might affect viral replication and reduce bats overall mobility and interactions, thereby decreasing the probability of virus transmission [ 27 ]. Contrary to our results, Subudhi et al (2017) found coronavirus persistence for up to 4 months in North American little brown bats during hibernation in laboratory settings [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Yearly and seasonal patterns in temperature and precipitation, referred to in biogeographic modelling as bioclimatic factors or predictors, are known to influence behaviour and life history in bats around the world (Conenna et al., 2019 ; Gorman et al., 2021 ; Kohyt et al., 2021 ; Weinberg et al., 2022 ). To capture these conditions and test the hypothesis that macroclimatic effects can determine occurrence of bats, the 19 standard current bioclimatic predictor variables were sourced at 2.5 arc‐minute resolution from the WorldClim v2.1 database for the period of 1970–2000 (Fick & Hijmans, 2017 ).…”
Section: Methodsmentioning
confidence: 99%